[69] A novel approach for the removal of an inflatable penile prosthesis - Abdalla Alhammadi (Taylor & Francis Group, 2018)
Objective: To describe a novel simple surgical method for the removal of an inflatable penile prosthesis (IPP), with minimal risk of urethral damage that avoids the penoscrotal incision and prevents additional fibrosis. The IPP has been used as definitive treatment for severe erectile dysfunction over last four decades. Although infection of IPPs is rare, such occurrences have critical clinical consequences and require urgent explantation. Removal of an IPP can be challenging, especially for the non-andrologist urologist and young urologists. Methods: Three incisions are made at the following sites: one incision on each side of the base of the penis, an inguinal incision, and a scrotal incision. Each incision provides direct access to one component of the IPP (cylinders, reservoir and pump). Conclusion: The classic penoscrotal incision for explanation can disrupt the anatomy, which makes future re-implantation difficult and increases the risks of complications. The present approach provides direct exposure of all components of the IPP without dissection of the adhesions of the previous implantation and reduces the risk of iatrogenic injury to the urethra.